Potential of Birch (Betula pendula Roth and B. pubescens Ehrh.) for Forestry and Forest-based Industry Sector within the Changing Climatic and Socio-economic Context of Western Europe - Dúbois, Heloise; Verkasalo, Erkki; Claessens, Hugues (MDPI, 2020)
Five commercial tree species comprise nearly 80% of the forest standing stock volume in Western Europe. Nowadays, there is a strong need to consider a wider diversity of tree species, as evidenced by the impact of climate change and the forest health crises over the past decades. In this context, this study focuses on the potential of birch (Betula pendula Roth and Betula pubescens Ehrh.), a neglected indigenous species, for forestry and the forest-based industry sector. We have therefore compiled, analyzed, and discussed literature regarding the strengths and weaknesses of the species and the opportunities and threats of its use for this purpose. Among the strengths, birch tolerates various climates and sites, and high genetic variability promotes its adaptability. Birch improves forest resilience by colonizing forest gaps and quickly increasing soil functioning and biodiversity. Birch is also remarkably resistant to game overpopulation-associated damage. Large-sized logs are produced within relatively short periods with proper silvicultural treatment, and the wood characteristics allow versatile and valuable uses, as shown in Northern Europe. However, its weaknesses include high sensitivity to crown competition and to wood rot as challenges for silviculture. Among the opportunities, birch is well-suited to the global changes with its adaptability to climate change and its possible integration in diverse productive mixed tree stands. In the context of societal evolutions and customer perceptions, birch wood could play an increasing role in the building and furniture sectors, and among non-wood forest products. In Western Europe, the main obstacle to birch development is the lack of information on the wood uses and, consequently, the lack of interest among forest managers and wood processing professionals, which have led to a poor quality of the resource and to insufficient demand for its wood. Moreover, its fast height growth can affect the vitality of other species in mixed stands. Our analysis highlighted the potential of birch in the Western European forestry considering societal, ecological, and economic purposes in a changing climatic and socio-economic context and the need to i) develop opportunities for industrial uses of birch wood, ii) inform forest owners, managers, and industrial professionals about the potential value of birch, and iii) define silvicultural guidelines.
Keywords: birches; global change; forestry; valuation market